A case report of unusual pneumomediastinum after endoscopic sinus surgery. (2016) - Alomari, Ahmad I.; Alzoubi, Firas Q.; Khatatbeh, Abdullah
Highlights: We report a case of rare and unusual complication of massive surgical emphysema involving orbit, face, neck and upper chest associated with pneumomediastinum in the first day post endoscopic sinus surgery. Pneumomediastinum should be suspected in if the patient develops a respiratory distress associated with massive periorbital, face and deep neck emphysema after endoscopic sinus surgery. Pneumomediastinum can be completely treated with conservative treatment. However, it can proceed to mediastinitis or septicemia and lead to the death. Abstract: Introduction: Endoscopic sinus surgery is a minimally invasive procedure used to restore normal sinus ventilation and mucociliary function. It is a routine otolaryngology procedure with a success rate of about 90% for symptomatic improvement in patients with refractory chronic rhinosinusitis. Because of the proximity of the paranasal sinuses to the brain and the orbit, it cannot be performed without a potential risk of complications. In our case, without early clinical suspicion, proper diagnosis and management, this unusual occurrence of pneumomediastinum after endoscopic sinus surgery may have led to major complications or even death. Presentation of case: We report a case of unusual mediastinal emphysema in a 53-year-old man after removal of the nasal pack on the day after endoscopic sinus surgery. Discussion: To the best of our knowledge, there are only two reported cases of mediastinal emphysema after endoscopic sinus surgery. What made our case unique was the absence of smoking history, pulmonary disease or infection and normal preoperative chest CT scan. We investigated further with postoperative chest CT scan, bronchoscopy and esophagoscopy to rule out anesthesia related laryngotracheal injury. In our case, the pneumomediastinum was successfully treated conservatively; however, it could have proceeded to mediastinitis, septicemia and death if it had not been diagnosed and treated early. Conclusion: Damage to the lamina papyracea can occur during endoscopic sinus surgery and presents as periorbital emphysema. Extension of the emphysema down to the mediastinum cannot be ignored as a possible etiology of the pneumomediastinum. Early diagnosis and proper management are important to avoid mortality.